Pengaruh Model Pembelajaran Learning Cycle 7E Berbantuan Media Powtoon Terhadap Aktivitas dan Hasil Belajar Siswa Kelas X SMA Negeri 4 Palu - Rahmadani, Nurlaila Wulan; Jamhari, Mohammad; Ashari, Abdul; Buntu, Amalia; Febriani, Vita Indri; Bialangi, Mursito S. (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to describe the influence of the model Learning Cycle 7E learning assisted by powtoon media on the activities and learning outcomes of class X students of SMA Negeri 4 Palu. The population in this study were all students of class X of SMA Negeri 4 Palu totaling 400 students spread across class X by taking a sample of 25% of the total, namely 70 students. Sampling used a purposive sampling technique, and the research sample was 2 classes consisting of class XE and XG. Data collection techniques used learning outcome tests and observation sheets. The results showed that there was a significant influence of student learning activities between the experimental class given the Learning Cycle 7E learning model treatment and the control class given the conventional learning model treatment. This is shown by the calculation of the observation sheet of student learning activities, student psychomotor activities and student affective activities in the experimental class getting a score of 83.54 percentage 81-100% very good category while in the control class getting a score of 77.64 percentage 61-80% good category and the average value of significant learning outcomes in class XE as an experimental class 82.20 and class XG as a control class 77.34. In addition, it is proven by the results of the hypothesis test (t-test), obtained a sig value in class X which is 0.00 <0.05. Thus, it can be concluded that the Learning Cycle 7E learning model assisted by Powtoon media has a significant effect on the activities and learning outcomes of class X students of SMA Negeri 4 Palu.